STRATEGI KOMUNIKASI RADIO DALKA FM MEULABOH DALAM DALAM MENINGKATKAN JUMLAH PEMASANG IKLAN - Rahma Hidayati; triyanto triyanto; masmidar masmidar (SOURCE : Jurnal Ilmu Komunikasi, 2018)
This research concludes that, Pull Strategy applied by Dalka FM is by looking for target ofadvertiser candidate, then send Dalka FM radio profile which inside is designed as possible.Another strategy is to include the price of the ad. It is intended that the advertiser becomesinterested in contacting and responding to the offer letter, or by visiting the prospect's businesspremises or face to face immediately and approaching to offer direct advertising. Push Strategyto encourage advertiser interest into a desire to work together by providing spot bonuses orviews for advertisers. Pass Strategy to expand marketing and create public opinion and positiveimage by holding events on air and off air, held events in the form of field activities to get closerto the community.Keywords: Communication Strategy, Dalka FM Radio, Advertisement.